Crossing the border - Koch, Dietrich-Alex (Neotestamentica, 2005)
It was a decisive step at the outset of early Christianity to cross the border that had divided Jews and Gentiles until then. This momentous decision was carried out in the Christian community in Antioch on the Orontes founded by the so-called "Hellenists", the Hellenistic Christian Jews who were driven out of Jerusalem. This step, however, can be explained as a consequence of the basic christological convictions that the "Hellenists" held already in Jerusalem. It is argued in this article, that these christological convictions are best recognized in the pre-Pauline tradition about Christ's expiatory death in Rom 3:25-26a. Christ's expiatory death is now the basis of the new people of God and has replaced the temple and the cultic atonement available there, especially the Day of Atonement. This proclamation was the reason for Stephen's martyrdom and the expulsion of the "Hellenists" from Jerusalem. In Antioch they crossed the border of Judaism. In baptizing Non-Jews they accepted them as members of the people of God only on the ground of their christological conviction that the dying and rising of Christ is the only basis for the people of God-and not the old foundations, neither the temple, nor the Torah, which had prohibited them until then from crossing the border. When Paul, for his part, joined the Christian community of Antioch, he shared these convictions and carried on the development that had its starting point in Antioch.